Turks and Caicos Islands : Assessment of the Supervision and Regulation of the Financial Sector-Review of Financial Sector Regulation and Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reviews Financial Sector Regulation and Supervision for Turks and Caicos Islands (TCI). The TCI has a structure for financial supervision that encompasses banking, insurance, mutual funds, investment brokers, trusts, trustees, companies' registration, and company service providers. The supervisory framework has undergone major modifications since 2000, but further strengthening of the legal and institutional framework is needed. The Financial Services Commission has been transformed into a statutory body and given additional autonomous powers for supervision. Underlying financial ordinances have been amended to bring them more in line with international standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet